Nutritional Evaluation of Cornflakes Waste in Diets for Broilers - Ayanwale, B.A.; Aya, V.E. (Pakistan Journal of Nutrition, 2006)
A nine week feeding trial was conducted to assess the nutritional value of cornflakes waste in broiler diets. Maize and cornflakes waste were used in various proportions as energy sources such that diets T 1 , T 2 , T 3 , T 4 and T 5 had maize at 100.0, 80.0, 60.0, 40.0 and 0.0 %; and cornflakes waste at 0.0, 20.0, 40.0, 60.0 and 100.0 % levels respectively. Data were collected on chemical composition of cornflakes waste and on the amino acid profile, nutrient digestibility, cooking loss and cooking yield of the meat from the broilers. Results showed that the cornflakes waste is higher in DM, CF and NFE but lower in CP, EE, ash, M.E. and methionine compared to maize. The highest nutrient digestibility was obtained in broilers fed 80.0% maize and 20.0% cornflakes waste mixture similar to the one from birds fed 100 % cornflakes waste as an energy source. This was an improvement over the digestibility of birds fed control diet at the starter phase. The results were attributed to the physicochemical changes that occurred during the processing of raw maize and other materials into cornflakes waste. Broilers fed 100 % cornflakes waste had higher (p< 0.05) cooking loss and lower cooking yield compared to birds fed the control diet. Diet T 2 with 80% maize and 20% cornflakes waste produced broilers with better meat quality due to its rigid structure as a result of the low cooking loss.